Вычислить производную y=(x^2 - 1) (x^4+2) По той формуле, что нам дал учитель (u x v)' =...

0 голосов
31 просмотров

Вычислить производную y=(x^2 - 1) (x^4+2) По той формуле, что нам дал учитель (u x v)' = u' v + v ' u получается: y'= (x^2 - 1)' x (x^4 +2) + (x^4 + 2)' x (x^2 - 1) Объясните, как считать дальше..


Алгебра (15 баллов) | 31 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

y=(x^2 - 1) (x^4+2); y'=((x^2 - 1) (x^4+2))'=\\ (x^2 - 1)' (x^4+2)+(x^2 - 1) (x^4+2)'=\\ (2x-0)(x^4+2)+(x^2-1)(4x^3+0)=\\ 2x(x^4+2)+(x^2-1)*4x^3=\\ 2x^5+4x+4x^5-4x^3=\\ 6x^5-4x^3+4x

(409k баллов)